2003
DOI: 10.1128/mcb.23.3.763-776.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dimer-Specific Potentiation of NGFI-B (Nur77) Transcriptional Activity by the Protein Kinase A Pathway and AF-1-Dependent Coactivator Recruitment

Abstract: The NGFI-B (Nur77) subfamily of orphan nuclear receptors (NRs), which also includes Nurr1 and NOR1, bind the NurRE regulatory element as either homo-or heterodimers formed between subfamily members. These NRs mediate the activation of pituitary proopiomelanocortin (POMC) gene transcription by the hypothalamic hormone corticotropin-releasing hormone (CRH), an important link between neuronal and endocrine components of the hypothalamo-pituitary-adrenal axis. CRH effects on POMC transcription do not require de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 104 publications
(136 reference statements)
10
160
1
Order By: Relevance
“…Since activation of the dopamine D 2 receptor normally reduces cAMP levels and striatal levels of NGFI-B (Gervais et al, 1999), blockade of the D 2 receptor by neuroleptics may increase or release inhibition of cAMP-dependent protein kinase activity (PKA) and result in an upregulation NGFI-B expression (Beaudry et al, 2000). Also, we cannot exclude that posttranslational modification (phosphorylation), which greatly affect NGFI-B activity (Maira et al, 2003), of pre-existing NGFI-B or de novo haloperidol-induced NGFI-B may play a role in the effects observed here. Other signaling pathways such as those implicating phospholipase C, intracellular calcium stores and protein kinase C (PKC) might also be involved (see Hernandez-Lopez et al, 2000).…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 98%
See 1 more Smart Citation
“…Since activation of the dopamine D 2 receptor normally reduces cAMP levels and striatal levels of NGFI-B (Gervais et al, 1999), blockade of the D 2 receptor by neuroleptics may increase or release inhibition of cAMP-dependent protein kinase activity (PKA) and result in an upregulation NGFI-B expression (Beaudry et al, 2000). Also, we cannot exclude that posttranslational modification (phosphorylation), which greatly affect NGFI-B activity (Maira et al, 2003), of pre-existing NGFI-B or de novo haloperidol-induced NGFI-B may play a role in the effects observed here. Other signaling pathways such as those implicating phospholipase C, intracellular calcium stores and protein kinase C (PKC) might also be involved (see Hernandez-Lopez et al, 2000).…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 98%
“…We have previously shown that acute haloperidol strongly increased NGFI-B mRNA levels in the rat forebrain (Beaudry et al, 2000), but the intracellular signaling events triggering by neuroleptics and leading to modulation of NGFI-B are unknown. It has been shown in vitro that NGFI-B is a direct target of kinases associated with G proteincoupled receptors intracellular signaling such as cyclic AMP (cAMP) and MAPK pathways (Kovalovsky et al, 2002;Slagsvold et al, 2002;Maira et al, 2003). Since activation of the dopamine D 2 receptor normally reduces cAMP levels and striatal levels of NGFI-B (Gervais et al, 1999), blockade of the D 2 receptor by neuroleptics may increase or release inhibition of cAMP-dependent protein kinase activity (PKA) and result in an upregulation NGFI-B expression (Beaudry et al, 2000).…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%
“…Additionally, RXR is highly versatile with respect to its heterodimerization; among the many other nuclear receptors with which it can interact are two members of the orphan nuclear subfamily, Nur77 and Nurr1. These factors also function independently by binding Nur‐response elements, as monomers (NBRE) and dimers (NurRE) (Maira et al, 1999; Maira et al, 2003; Lefebvre et al, 2010). nFGFR1 forms CBP‐containing low mobility chromatin complexes with RXR, RAR, and Nurs.…”
Section: Ontogenic Programing Of Esc—role Of Ramentioning
confidence: 99%
“…In fact, in this study, TRP1 promoter activity was strongly stimulated by both Nurr-1 and Nur77. Although the induction of Nurr-1/Nur77 expression was not so strong, it has been reported that CRF not only induces Nurr-1/Nur77 but also modulates dephosphorylation of the proteins (Maira et al, 2003). Therefore, the effects of Nurr-1/Nur77 on TRP1 gene expression levels may also be affected by the qualitative level through, for example, dephosphorylation of Nurr-1/Nur77.…”
Section: Discussionmentioning
confidence: 99%